(Post)colonial voices at Fort Jesus, Kenya - Sarmento, João Carlos Vicente (2011)
The principal aim of this chapter is to examine how a particular group of local tourist guides at Fort Jesus deals with the presentation and interpretation a colonial building, in relation to international audiences. These performances are framed under the pressures of daily life and the complex political and cultural contemporary situation in Kenya. My analysis and narrative is constructed from on-site experience in the summer of 2007, partly undertaken as a tourist and partly as a researcher. The primary source of material relates to semi-structured interviews conducted at the Fort’s entrance with 10 tourist guides. Formal and informal interviews were also made with some of Fort Jesus administrators. Finally, informal talks with tourists helped to construct this analysis. The archive of the Fort Jesus Library was visited on several occasions and various other coastal resorts, from Malindi to Diani Beach, were also visited.